2021
DOI: 10.5114/reum.2021.103436
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of retinal changes in patients with systemic sclerosis: the association between retinal vascular changes and nailfold capillaroscopic findings

Abstract: Background Systemic sclerosis (SSc) is a connective tissue disease affecting the skin and multiple organs. Most of the evidence on ocular involvement comes from small studies. We evaluated the retinal vascular changes in patients with SSc and its associations with types, disease duration, skin score, and nailfold capillaroscopy changes. Material and methods We evaluated the demographic, clinical and nailfold capillaroscopy data of 52 patients referring to the clinic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This is the first structured case-control study to explore retinal changes in IIM. Previous studies affirm the presence of exhibit retinal vascular changes such as cotton wool spots, retinal hemorrhages, and vascular tortuosity in up to 10% of SLE patients and a third of systemic sclerosis patients respectively ( 14 , 15 ). The comparable findings of retinal abnormalities in IIM patients may be attributed to either accelerated atherosclerosis, vasculitis, or vasculopathy.…”
Section: Discussionmentioning
confidence: 71%
“…This is the first structured case-control study to explore retinal changes in IIM. Previous studies affirm the presence of exhibit retinal vascular changes such as cotton wool spots, retinal hemorrhages, and vascular tortuosity in up to 10% of SLE patients and a third of systemic sclerosis patients respectively ( 14 , 15 ). The comparable findings of retinal abnormalities in IIM patients may be attributed to either accelerated atherosclerosis, vasculitis, or vasculopathy.…”
Section: Discussionmentioning
confidence: 71%
“…[14] Another study concluded there was no correlation between them and that the mechanism of change in retinal microvasculature and the nail folds are different. [15] Erturk and coauthors compared the OCT-A ndings in systemic sclerosis patients with patients with Raynaud's phenomenon. They found that the whole, parafoveal, and perifoveal SCP and DCP vessel densities were higher in patients with Raynaud's.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small number of patients in each group, this issue requires further investigation. Shenavandeh et al assessed retinal vascular changes in SSc patients, but found no evidence of a relationship between retinal vascular changes seen on fundus photography and SSc patterns upon NFC ( 56 ). However, this cannot be related to our study due to the functional and structural heterogeneity of retinal and choroidal circulation ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%